D-dimer and the Risk of Stroke and Coronary Heart Disease - Zakai, Neil A.; McClure, Leslie A.; Judd, Suzanne E.; Kissela, Brett; Howard, George; Safford, Monika M.; Cushman, Mary (Thrombosis and Haemostasis, 2017)
D-dimer, a biomarker of coagulation, is higher in blacks than in whites and has been associated with stroke and coronary heart disease (CHD). It was our objective to assess the association of higher D-dimer with stroke and CHD in blacks and whites. REGARDS recruited 30,239 black and white participants across the contiguous US and measured baseline D-dimer in stroke (n=646) and CHD (n=654) cases and a cohort random sample (n=1,104). Cox models adjusting for cardiovascular risk factors determined the hazard ratio (HR) for increasing D-dimer for cardiovascular disease with bootstrapping to assess the difference in HR for CHD versus stroke by race. D-dimer was higher with increasing age, female sex, diabetes, hypertension, pre-baseline cardiovascular disease and higher C-reactive protein (CRP). Accounting for cardiovascular risk factors, each doubling of D-dimer was associated with increased stroke (hazard ratio [HR] 1.15; 95 % confidence interval [CI] 1.01, 1.31) and CHD (HR 1.27; 95 % CI 1.11, 1.45) risk. The difference in the HR between CHD and stroke was 0.20 (95 % CI >0.00, 0.58) for blacks and 0.02 (95 % CI –0.30, 0.27) for whites. CRP mediated 22 % (95 % CI 5 %, 41 %) of the association between D-dimer and CHD and none of the association with stroke. Higher D-dimer increased the risk of stroke and CHD independent of cardiovascular risk factors and CRP, with perhaps a stronger association for CHD versus stroke in blacks than whites. These findings highlight potential different pathophysiology of vascular disease by disease site and race suggesting potential further studies targeting haemostasis in primary prevention of vascular disease.
Keywords: Continental population groups; coronary disease; D-dimer; epidemiology stroke